Association between exposure to 35 environmental pollutants and mortality from cerebrovascular diseases: A long-term prospective study - Lingjun Yan; Bingqin Xie; Zilin Liu; Yu Huang; Chenyu Ding; Wenhua Fang; Fuxin Lin; Yuanxiang Lin; Dezhi Kang; Fa Chen (Ecotoxicology and Environmental Safety, 2025)
Environmental pollutants have been implicated in various detrimental health effects. However, the specific relationship between environmental pollutant exposure and the risk of cerebrovascular disease mortality remains uncertain. This study aimed to comprehensively explore the potential relationship between environmental pollutant exposure and risk of cerebrovascular disease mortality in the U.S. population. Data on 35 types of environmental pollutant exposure were extracted from the National Health and Nutrition Examination Survey (NHANES). Cerebrovascular disease-related deaths were ascertained from the National Center for Health Statistics, with mortality follow-up data available until December 31, 2019. Weighted univariable and multivariable Cox regression analyses were employed to evaluate the association between environmental pollutants and mortality from cerebrovascular diseases. A total of 11,643 participants were included for organochlorine pesticides, 11,912 for brominated flame retardants, 13,797 for per- and polyfluoroalkyl substances, and 14,560 for phthalates, with a median follow-up of 8.6 years. The average age of participants was approximately 46 years, with male participants comprising around 48 % of the cohort. Four types of organochlorine pesticides (hexachlorobenzene, oxychlordane, 2,2-Bis(4-chlorophenyl)-1,1-dichloroethene, and trans-nonachlor), perfluorooctanoic acid, and mono-n-butyl phthalate were found to be associated with an increased risk of cerebrovascular disease mortality. Furthermore, the composite environmental index derived from these six pollutants also demonstrated a significant correlation with elevated cerebrovascular disease mortality risk. This prospective study provides evidence of an association between certain environmental pollutant exposure (especially for organochlorine pesticides) and risk of cerebrovascular disease mortality. These findings provide new insights into potential prevention strategies for this disease mortality from the perspective of environmental pollutant exposure.